Calibration of GPS Instruments using GPS Network Test for High Accuracy Application - Muhammad Zahied Bin Mohd Noor , Muhammad Zahied (Universiti Teknologi Petronas, 2009)
The objectives of this project are to perform the calibration procedures on the GPS instruments and to check the accuracy and precision of them. By using the GPS Network Test, the accuracy and precision of the equipment could be checked and analyzed. Application of GPS is extensively used nowadays. GPS can be used for many applications such as land application, air application, marine application, space application and military application. The important used of GPS which to get precise and accurate results is made it necessary for the equipment to carry out the calibration. Scope of study for this project covers the topics which are the studies of GPS receiver, GPS control station, GPS surveying procedures and GPS data processing. Steps or procedures involve in this projects are the selection of GPS control stations, fieldwork planning, conducting GPS surveying or observation, processing the GPS data, analyzing the results and discussion over the results. At the end of this project, a certain recommendation will be made for the GPS instrument based on the analysis of results obtained from the calibration procedures